PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF ONLINE BERBANTUAN DESMOS PADA KELASKITA MATERI PROGRAM LINIER KELAS XI SMA - Kusumaningtyas, Nastiti; Trapsilasiwi, Dinawati; Fatahillah, Arif (Kadikma, 2018)
This research aims to develop a Desmos-assisted interactive online instructional media using “Kelas Kita” on Linier Program material. The instructional media being developed is Desmos-assisted “Kelas Kita”. The research was conducted at SMA 3 Muhammadiyah Jember on eleventh grade students of IPA 2. This research is a developmental research. This research applied Thiagarajan model which consists of 4 stages namely: 1) Defining stage 2) Designing stage 3) Developing stage 4) Disseminating stage. The development results of this research includes validity test of validation sheet analysis from 3 validation tools. The assessment results from the validation tools showed the very high category in details of an average value of 0.89. The practicality test based on the user response questionnaire showed the very practical category with an average value of 1.7 or at a percentage level of 85%. This media achieved the very effective category 28 from 34 students acquired scores more than or equivalent to the minimum criteria of mastery learning. The results of the effectiveness showed that the eleventh grade students of IPA 2 who completed the test were about 82.85% of the students. Based on the research result, it showed that the media used have met the validation, practicality, and effectiveness criteria. Therefore, it is assumed that this media is feasible to be used as an instructional media. Keywords: Kelaskita, Desmos, Learning Media